Covid-19 screening with GeNose for Ramadan blood donation during the pandemic - Basuki Supartono; Prita Kusumaningsih; Zakiyyah Zakiyyah; Sarah Primadani Kaurow (Universitas Muhammadiyah Magelang, 2022)
During the Covid-19 virus pandemic, the demand for blood for transfusions in hospitals has not decreased and is even increasing. Meanwhile, the availability of blood at PMI has decreased, particularly as Ramadan approaches. This activity aims to meet blood needs by allowing people to donate blood in a safe and comfortable manner. This activity was carried out by following strict health protocols and using GeNose to screen for Covid-19. Three donors did not meet the requirements due to their Hb levels and history of Hepatitis infection, despite registering and passing the Covid-19 screening, so only 31 bags of blood were obtained. The donors ranged in age from 19 to 60 years old, with the majority being in the pre-elderly age group. The donor was pleased, and he encouraged others to participate in donor activities at a later date. The blood donation was completed in a safe and comfortable manner, with no reports of post-blood donation infection due to the corona virus from either the donor or the committee